2021
DOI: 10.1001/jamanetworkopen.2021.36364
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race and Ethnicity With Prostate Cancer–Specific Mortality in Canada

Abstract: Despite extensive research, age, family history, race and ethnicity, and certain genetic sequence variants remain the only currently well-established risk factors for prostate cancer. Black men are purported to have an increased risk of early and aggressive prostate cancer. This higher risk classification for Black men has resulted in recommendations for earlier prostate cancer screening and evidence of distinctive treatment patterns. 1,2 However, the underlying data for these recommendations lack high-quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…32 A recent cohort study found no increase in prostate cancerspecific mortality among Black people in Canada after adjusting for nonbiological differences such as socioeconomic status and access to health care. 33 This finding contradicted earlier studies that proposed genetic differences as a major cause for elevated risks of prostate cancer in Black people. 19,20 It is, however, likely that genetic ancestry and societal barriers intersect, and further research is required to draw out such nuances.…”
Section: How Do the Social Determinants Of Health Affect Prostate Can...mentioning
confidence: 67%
“…32 A recent cohort study found no increase in prostate cancerspecific mortality among Black people in Canada after adjusting for nonbiological differences such as socioeconomic status and access to health care. 33 This finding contradicted earlier studies that proposed genetic differences as a major cause for elevated risks of prostate cancer in Black people. 19,20 It is, however, likely that genetic ancestry and societal barriers intersect, and further research is required to draw out such nuances.…”
Section: How Do the Social Determinants Of Health Affect Prostate Can...mentioning
confidence: 67%
“…43 The studies were published between 2007 and 2021, with seven being published in the past 5 years. [35][36][37]39,42,44,45…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…33,34,46,47 Six studies focused on immigrant populations 35,37,38,41,44,48 and three on ethnic or racial minorities. 32,45,49 The remainder of the studies assessed population-wide data that contained information concerning Black individuals. 36,39,40,42,43,50 Results on general aspects of cancer (not specified/ various)…”
Section: Targeted Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…TP53 mutation affecting 50% of metastatic PCa cases are well known to serve as a prognostic biomarker of PCa, especially CRPC [ 8 ]. However, there remains conflicting results regarding the implementation of biomarker signatures, especially given variance between different ethnicities and the search for an effective biomarker continues [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%